2017
DOI: 10.1038/srep40133
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase c-Abl regulates the survival of plasma cells

Abstract: Tyrosine kinase c-Abl plays an important role in early B cell development. Its deletion leads to reduced pro- and pre-B cell generation in mice. However, its function in B cell terminal differentiation remains unexplored. Here, we used c-Ablf/f Aicdacre/+ mice, in which c-Abl is ablated only in antigen-activated B cells, to study the role of c-Abl in germinal center (GC) B and antibody-secreting plasma cell formation. Upon challenge with a model antigen, we found normal GC and memory B but reduced plasma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…a new transcriptional cell program). Finally, overexpression of ABL1 confirms previous observations by Li et al ( 43 ) which revealed the role of this tyrosine kinase on PC survival.…”
Section: Discussionsupporting
confidence: 90%
“…a new transcriptional cell program). Finally, overexpression of ABL1 confirms previous observations by Li et al ( 43 ) which revealed the role of this tyrosine kinase on PC survival.…”
Section: Discussionsupporting
confidence: 90%
“…In our previous work, we summarized that ROS may regulate the expression of ABL1 by triggering receptor tyrosine kinases (RTKs), which subsequently led to the phosphorylation of ABL1. NF- κ B1 and STAT3 were the main factors involved in cytokine release [29, 30], and both NF- κ B1 and STAT3 were proven to be downstream targets of ABL1 in leukemia [31, 32]. Here, we treated SGC-7901 and AGS GC cell lines with different concentrations of H 2 O 2 (0 μ M, 25 μ M, and 50 μ M), and the result showed that ROS could enhance the activities of ABL1 and could upregulate p-NF- κ B1, p-STAT3, IL-6, IL-1 β , and COX2 (Figure 2(a)).…”
Section: Resultsmentioning
confidence: 99%
“…NF- κ B1 and STAT3 are crucial factors regulating the tumor microenvironment. Both NF- κ B and STAT3 are proven to be downstream targets of ABL1 in leukemia [31, 32]. The constitutive activation of NF- κ B1 leads to cytokine release (TNF α , IL-6, IL-1, and IL-8), and these cytokines can give a positive feedback loop to induce the activation of NF- κ B [3840].…”
Section: Discussionmentioning
confidence: 99%
“…For example, T cells in Bim-deficient mice are defective in TCR-induced activation and IL-2 production due to impaired calcium signaling (72). Additionally, T cell development is impaired at the DN to DP stages in the thymus altering T cellular composition and repertoire in the Bim-deficient mice (73). Alternatively, global loss of Bim in the whole body reduces release of self-antigens from dead and dying host cells that trigger autoimmune response.…”
Section: Discussionmentioning
confidence: 99%